A case study of applying collective technical-tactical performance goals in elite men`s volleyball team - Palao, J. M.; Garcia-de-Alcaraz, A.; Hernandez-Hernandez, E.; Ortega, E (International Journal of Applied Sports Sciences, 2016)
The purpose of this study was to test a protocol for establishing collective technical and tactical performance goals in elite men`s volleyball. The participants were a professional volleyball team. The period of study was one entire season. A baseline was established in the first half of the season, and the intervention was carried out in the second half of the season. The intervention involved the use of seven collective performance goals for monitoring the team in competitions. The variables studied were: the achievement of the collective performance goals that were established; the game phase; the result of the set; and the players`, coaches`, and psychologist`s perception of the use of the performance goals and the poster. The team slightly increased the number of goals achieved per game in the intervention period. There was a significant reduction in serve errors and a significant increase in block contacts. The intervention increased the players` engagement with the team, although there were differences in opinion about the effect on the different players. The intervention improved the players' understanding of the match. The effects of the goal-setting and the poster were positively perceived, due to helping the players to understand their needs and the aspects to improve.